Make Scale Invariant Feature Transform “Fly” with CUDA - Yuhong Mo; Chaoyi Tan; Chenghao Wang; Hao Qin; Yushan Dong (International Journal of Engineering and Management Research, 2024)
This paper introduces an implementation of scale invariant feature transform (SIFT) algorithm with CUDA. Primary steps including building the Gaussian pyramid and the difference of Gaussian pyramid, identification, localization [1], and orientation generation of key-points are realized on GPU with CUDA. A detailed description of important kernel function implementations is covered along with optimizations made to achieve high performance, and a comparison between the CUDA version SIFT algorithm and a baseline sequential CPU implementation is included.